PERANAN POLISI LALU LINTAS DALAM MENGAWASI PENGGUNAAN HELM OLEH PENGENDARA SEPEDA MOTOR DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Laili, Mayzatul; Indra, Mexsasai; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The use of a helmet is an obligation for the safety of motorists, it is set in article 57 of the Act number 22 in 2009 that supplies of motor vehicles for a motorcycle helmet is a Standard National Indonesia (SNI). But there are still many motorists who break the law and do not understand the importance of using protective tool head while riding his motorcycle in the town of Pekanbaru.The purpose of this study, to find out the role of the police traffic in overseeing the use of helmets and to know the obstacles faced by traffic police in law enforcement against violations of the use of helmets as well as to know the settlement effort conducted by the traffic police against violation of the use of helmets by motorcyclists in the region Police Law of the resort city of Pekanbaru.This research was conducted by using the approach of observation research that is by way of a survey or review the immediate kelokasi research using data that is collecting interviews, then the method used is a sociological researcher with a view of the study of documents and studies field. While the nature of this research is descriptive research, namely the author tried to give an overview in detail about the role of the Police traffic in overseeing the use of helmets by motorcyclists in the region Police Law of the resort city of Pekanbaru.From the results of the research there were three basic problems that can be inferred. First, the role of the Police in the region of Soweto City resort of the law against the duty of every motorist should use helmets. Prevention efforts by giving the Socialization and education of traffic as well as providing warnings about the importance of complying with traffic signs. Second, restricting factors faced by traffic police in law enforcement against violations of the use of Helmets from internal factors at the time of carrying out law enforcement in the city of Pekanbaru in the exercise of his duties and external factors occur due to the very low legal awareness of motorcyclists in the city of Pekanbaru. Third, breach of the obligation of Prevention Efforts wear a helmet every motorist is very important as prevention of occurrence of kecelaakaan traffic. the rule of law governing the liability of using a safety helmet drive had been issued but in practice many still motorists who ignore the regulations. The authors suggestion, first, the role of the police in the legal obligation of meneggakkan wear a helmet shall be executed in accordance with the provisions of the applicable legislation. Second, the head of the Police Traffic Unit of the resort town of Pekanbaru is necessary to increase public awareness of the obligation to wear a helmet. Third, To motorists in order to obey the obligation to wear a helmet to avoid road accident luntas.Key words: the role of the Police-the use of helmet-Motorcycle Riders